Eastman Sokolov : the search for a strategic investor - Bauer, Michal; Streblov, Pavel; Nollen, Stanley (London : NeilsonJournals Publishing, 2005)
Eastman Sokolov is a sizable Czech chemical company that made the transition successfully from central planning to market economy. The case traces the key events at the company (Chemicke? Za?vody Sokolov until 2000) from 1991 to 2000, with a two-fold focus on the actions of the top manager to restructure the company and to find a strategic investor amidst adverse business conditions. We examine three offers to acquire CZS that that were rejected as well as the final successful offer from Eastman Chemical Co. We investigate the top manager's background, the starting conditions he faced, the external market forces that acted on the company, and the actions of the central government that affected it.
Originally Published InBauer, M., Streblov, P., & Nollen, S. (2005). Eastman Sokolov: The search for a strategic investor. Journal of International Business Education, 2(1), 39-52. JIBE2-0CS1.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Eastman Sokolov -- Case studies; Central planning -- Czech Republic -- Case studies; Business enterprises -- Czech Republic -- Case studies